2009
DOI: 10.1002/jccs.200900049
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration of Rare Earth Elements in Seawater with Chelating Resin Having Fluorinated β‐Diketone Immobilized on Styrene Divinyl Benzene for their Determination by ICP‐OES

Abstract: An analytical method has been developed for the preconcentration of rare earth elements (REEs) in seawater for their determination by inductively coupled plasma optical emission spectrometry (ICP-OES). An indigenously synthesized chelating resin was used for the preconcentration of (REEs) which was based on immobilization of fluorinated b-diketone group on solid support styrene divinyl benzene. Sample solutions (adjusted to optimized pH) were passed through a polyethylene column packed with 250 mg of the resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In the paper by De Vito et al (1999) it was found that Amberlite XAD-7 resin with (o-[3,6-disulpho-2-hihydroxy-1-naphthylazo]-benzenearsonic acid) was successfully used for the separation and preconcentration of Sm(III), Eu(III) and Gd(III). The resin containing the fluorinated--diketone chelating group immobilized on solid support styrene divinyl benzene was applied for the simultaneous preconcentration of La(III), Ce(IV), Nd(III), Sm(III), Gd(III), Eu(III), Dy(III), Er(III), Yb(III) and Lu(III) (Rao & Kala, R. 2004;Waqar, et al 2009). Preconcentration of La(III), Eu(III) and Yb(III) was also achieved by sorption of their 1-phenyl-3-methyl-4-benzoylpyrazol-5-one (PMBP) complexes on a silica gel column (Liang & Fa, 2005).…”
Section: Separation Using Chelating Ion Exchangersmentioning
confidence: 99%
“…In the paper by De Vito et al (1999) it was found that Amberlite XAD-7 resin with (o-[3,6-disulpho-2-hihydroxy-1-naphthylazo]-benzenearsonic acid) was successfully used for the separation and preconcentration of Sm(III), Eu(III) and Gd(III). The resin containing the fluorinated--diketone chelating group immobilized on solid support styrene divinyl benzene was applied for the simultaneous preconcentration of La(III), Ce(IV), Nd(III), Sm(III), Gd(III), Eu(III), Dy(III), Er(III), Yb(III) and Lu(III) (Rao & Kala, R. 2004;Waqar, et al 2009). Preconcentration of La(III), Eu(III) and Yb(III) was also achieved by sorption of their 1-phenyl-3-methyl-4-benzoylpyrazol-5-one (PMBP) complexes on a silica gel column (Liang & Fa, 2005).…”
Section: Separation Using Chelating Ion Exchangersmentioning
confidence: 99%
“…In our earlier work, we have characterize locally synthesized chelating resin based on immobilization of fluorinated beta diketone group on solid support styrene divinyl benzene (SDVB) for the pre‐concentration of light, medium and heavy rare earth elements (La, Ce, Nd, Sm, Eu, Gd, Dy, Er, Yb and Lu) in coastal sea water samples 32. In this work, the resin was investigated for the simultaneous extraction/pre‐concentration of Cd, Co, Fe, Mn, Mo, Ni and Zn in natural water samples of various origins including Dam, River and Tap water.…”
Section: Introductionmentioning
confidence: 99%
“…Various adsorbent such as polymer materials [7,8], carbon materials [9,10], and silica materials [11,12] have been studied. To selectively adsorb REEs, small molecules bearing chelating groups such as β-diketone [13], EDTA [14], are often used to modify the material surface. Diglycolamide (DGA), containing ether linkages between two amide groups, display high affinity for REEs and have been used as extractant [15,16].…”
Section: Introductionmentioning
confidence: 99%